Employee Empowerment and Organisational Effectiveness in Electricity Distribution Firms in Rivers State - Yakubu, Justina Inusah Gideon (PhD); Offiong, Vivian Agustine (PhD) (Genius Journals, 2024)
This study examined the relationship between employee empowerment and organisational effectiveness in electricity distribution firms in Rivers State. The target population for this study comprises all managers and supervisors of electricity firms in Port Harcourt, Rivers State. However, accessible population was made up of thirty-five (35) employees of electricity distribution firms in Rivers State at the convenience of the researcher. Sample size of 35 was adopted from the total population drawn using census study. Two (2) testable null hypotheses were formulated and analyzed. Spearman’s Rank Order Correlation Coefficient was used to analyze the null hypotheses, with the help of Statistical Package for Social Sciences at 5% level of significance. The two null hypotheses were rejected and the alternate accepted. Indicating a significant positive relationship between the dimensions of employee empowerment (training and delegation) and organizational effectiveness. Consequently, it was recommended that management of electricity firms should; Management of electricity distribution firms should implement a comprehensive training program for leaders within electricity firms, emphasizing both technical and soft skills, and also collaborate with training institutions and industry experts to design a tailored leadership development program. Management of electricity distribution firms should ensure to foster a culture of effective delegation by providing leaders with the tools and support needed for successful task allocation and equally encourage leaders to delegate tasks based on employees' strengths and provide feedback on the delegation process
Keywords: Organisational Effectiveness; Employee Empowerment